Warning: Extinction Ahead! Theorizing the Spatial Disruption and Place Contestation of Climate Justice Activism - Axon, Stephen (Environment, Space, Place, 2019)
Since 31 October 2018, Extinction Rebellion has advocated in numerous examples of civil disobedience across the UK in an attempt to call for further action to address climate change. Following this example, similar activism has also been seen across Europe and North America. Such activism falls within the context of climate justice (the framing of climate change as an ethical and political issue); given the disproportionate impacts that climate change has on the most vulnerable people in society, e.g., low-income communities, women, and future generations. What is noticeable about Extinction Rebellion is its ability to place climate change on the social agenda, a task that has proven difficult in the age of denialism, skepticism, false-balance media reporting, and far-right politics. With reference to recent examples of civil disobedience and protests in 2019, this paper evaluates how climate justice movements, specifically Extinction Rebellion, change meanings of urban landscapes into becoming more contested places and disrupt the consciousness of everyday routines toward sustainability. This disruption and contested nature is brought about through changing the sociocultural dynamics of urban landscapes during, and after, such protests. The meanings of urban landscapes thus change from being viewed as purely sites of materialist consumption to sites of initial resistance against business-as-usual approaches to climate change leading to changes in policy. Through substantial public engagement with the narrative of climate justice, civil disobedience protests, and urban art, it is clear that urban areas “held” for a number of successive days have started to be perceived differently. This article concludes with implications for subsequent spatial disruption and civil disobedience advocating for stronger climate policy.
Keywords: dept.egm; peer-reviewed